(untitled) (Damascus University Journal for engineering sciences, 2022)
Syria is witnessing an increase number of mega-scale, more sustainable housing projects. This is due to these projects role in: meeting the increased demand for housing, creating new jobs, encouraging investments and moving the wheel of the post-war economy. Sustainable projects contribute to better level of buildings standards and to improved performance of the construction companies, due to the strict sustainable project management procedures throughout the project life cycle phases. In contrast, the implementation of sustainable projects appears to be riskier than traditional projects due to the high technical requirements and to the innovative construction processes. For Syria mega-scale residential projects, achieving sustainability is characterized by the need for high design knowledge, sufficient technical skills, management capabilities, and high investments. These enablers are limited in light of reconstruction local efforts. As a result, the weak performance of reconstruction companies has led to widening the quantitative and qualitative gap in meeting the increased demand for housing. The traditional performance of construction companies is new to the sustainability concept challenges with an urgent need to improve in order to cooperate with international future investments on the announced mega-scale residential projects. The research aims to identify and assess sustainability risks and mitigation measures in Damascus mega-scale residential projects. The study survey targeted local construction companies (from the public, private and Public Privet Partnership PPP sectors) involved in Damascus mega-scale residential projects. Data are analyzed and weighted using PMI method. The findings present the most severe risks: increased expenditures than expected, lack of green materials and equipment, lack of social and alternative housing insurance, unclear distribution of responsibilities, and shortage of qualified professionals. Besides, the most effective responses found are: "good preparation of contract specifications 4.27" and "commitment to timely decision-making and implementation 4.07". These findings are significant as this is the first-hand experience gathered from Damascus reconstruction projects. Identifying and assessing sustainability risks is the key step in managing sustainability risks. This research adds novel insights into residential projects sustainability drivers on SRM which will positively affect post-war construction companies as a turning point from traditional to sustainable housing.